Psychological features of patients with pathology of the digestive organs - Korshevnyuk, Дмитро; Syropiatov , Олег (Psychosomatic Medicine and General Practice, 2021)
The theses consider the main theoretical principles of psychopathological aspects and personality types in patients with peptic ulcer pathology of the digestive system. The direction of further scientific researches is planned: to study features of a course of mental displays at patients with a peptic ulcer pathology of digestive organs in modern conditions.